Prevalence and associated factors of at risk of anemia among children under five in Northeast Thailand using noninvasive hemoglobin screening in a cross sectional study - Suchaorn Saengnipanthkul; Prapassara Sirikarn; Sasupang Musikaboonleart; Ly Cong Tran; Maneerat Puwanant (Scientific Reports)
Abstract Pediatric anemia remains a significant public health challenge in Northeast Thailand, where hemoglobinopathies and nutritional deficiencies coexist. Early identification of children at risk of anemia is crucial to prevent developmental and health consequences. This study assessed the prevalence of children under five being at risk of anemia using Masimo Rad-67® with Rainbow DCI-mini Sensor, while evaluating the association between caregivers’ knowledge, attitudes, and practices on complementary feeding and childhood anemia. A clustered randomized cross-sectional study was conducted involving 2,000 child-caregiver pairs (aged 6 months to 5 years) in Northeast Thailand from September 2022 to March 2023. Non-invasive hemoglobin measurement was used, with anemia risk defined as spectrophotometry hemoglobin (SpHb) < 13.0 g/dL. Data collection included demographic characteristics, natal history, and feeding practices. Additionally, a survey was conducted to assess associated factors of anemia and caregivers’ attitudes, knowledge, and practices regarding complementary feeding. The study found a 36.9% prevalence of at-risk anemia. Key predictors included age under 24 months (adjusted OR 2.1, 95%CI 1.7–2.6), maternal thalassemia trait (adjusted OR 1.8, 95%CI 1.4–2.3), and wasting (adjusted OR 1.6, 95%CI 1.2–2.1). Iron supplementation was a protective factor. Despite 48.2% of children receiving iron supplementation per government policy, only 24.6% met the daily iron intake according to the Thai dietary reference intake. Gap in caregiver knowledge persisted, with 68.1% of caregivers having received education on iron deficiency anemia, and only 32% able to name iron-rich foods. Public health strategies should combine nutritional education targeting iron-rich complementary feeding, implementation of a thalassemia-integrated screening protocol, and proactive community surveillance programs to improve iron intake. Thai clinical trial registration: TCTR20221024002.